Paradiplomacy from five perspectives: theoretical reflexions for the construction of an epistemic community in Latin America - Oddone, Nahuel (2016)
Transformation processes experienced in the international arena have led to bestow higher priority to transnational issues, as well as greater recognition of non-state actors in regard to its influence on world politics. These processes, to change the international scope, initially are originated within a nation-state, from the sub-national and sub-state component. Starting from this, is introduced the concept of paradiplomacy, which involves the participation of non-central governments in the field of international relations, with the aim of promoting different dimensions that go beyond the internal constitutional policy, as in economic aspects, cultural aspects, etc. Thereby, paradiplomacy demonstrates to be an important piece for each country in the international system, which is capable of modifying intergovernmental relations, transnational relations, foreign policies and structures of integration. For its relevance, paradiplomacy is analyzed from five theoretical perspectives: 1) international actor; 2) foreign policy and decision-making processes; 3) territorial development; 4) regional integration and 5) governance.